2015
DOI: 10.1177/000313481508100432
|View full text |Cite
|
Sign up to set email alerts
|

Use and Accuracy of Computed Tomography Scan in Diagnosing Perforated Appendicitis

Abstract: Perforated appendicitis has major implications on patient care. The ability of computed tomography (CT) scan to distinguish perforation in the absence of phlegmon or abscess is unknown. The purpose of this study is to assess the use and accuracy of CT scans in diagnosing perforated appendicitis without phlegmon or abscess. A retrospective chart review of 102 patients who underwent appendectomy from 2011 to 2013 was performed. Patient demographics and operative and postoperative course were recorded. Two radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The recommendations for the use of antibiotic treatment alone is limited to cases of acute uncomplicated appendicitis; diagnosis on the basis of imaging results, which are fallible. Verma et al found that computed tomography, the most common and gold‐standard imaging test, only had a 38% sensitivity for identification of perforation in the absence of phlegmon or abscess, and Leeuwenburgh et al showed that magnetic resonance imaging or ultrasound with conditional use of CT scan incorrectly identified perforated appendicitis as uncomplicated cases in up to half of the cases. The distinction between complicated and uncomplicated appendicitis is crucial, as prior studies have shown that the rates of appendiceal malignancy are much higher in complicated cases compared with uncomplicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendations for the use of antibiotic treatment alone is limited to cases of acute uncomplicated appendicitis; diagnosis on the basis of imaging results, which are fallible. Verma et al found that computed tomography, the most common and gold‐standard imaging test, only had a 38% sensitivity for identification of perforation in the absence of phlegmon or abscess, and Leeuwenburgh et al showed that magnetic resonance imaging or ultrasound with conditional use of CT scan incorrectly identified perforated appendicitis as uncomplicated cases in up to half of the cases. The distinction between complicated and uncomplicated appendicitis is crucial, as prior studies have shown that the rates of appendiceal malignancy are much higher in complicated cases compared with uncomplicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…While accuracy of simple appendicitis is high, CT is far from perfect when identifying perforation with a specificity of 38% [13]. In addition, there is a discordance between surgeons, radiologists, and pathologists regarding the classification of perforation, which has been reported as high a 11.6% [14].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, stopping CT for the diagnosis of appendicitis may result in incorrect or delayed treatment and subsequently patient harm. Although CT should be considered low value, it may well be that the expertise for accurate ultrasonography, which is heavily operator dependent, is not readily available (particularly out of hours).…”
Section: Discussionmentioning
confidence: 99%